1999
DOI: 10.1177/088307389901401011
|View full text |Cite
|
Sign up to set email alerts
|

Parasagittal Cerebral Injury: Magnetic Resonance Findings

Abstract: Parasagittal cerebral injury is a specific pathologic lesion that can be found in full-term newborn babies suffering from hypoxic-ischemic encephalopathy. It is defined by the presence of cortical and subcortical white-matter necrosis involving the parasagittal and superomedial areas of the cerebral convexities. We report on two patients who showed parasagittal cerebral injury on magnetic resonance imaging. In both cases antecedents of hypoxic-ischemic encephalopathy were noted. In one of the patients basal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…8,15 The watershed regions in premature infants are located between the ventriculopetal and ventriculofugal arterial systems and, therefore, hypoxic-ischemic lesions in this age group are mainly concentrated in periventricular regions (periventricular leukomalacia). In term newborns, the vascular border lies between the anterior and middle and the middle and posterior cerebral arteries in the cortex, a distribution that corresponds to that of parasagittal injury.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 The watershed regions in premature infants are located between the ventriculopetal and ventriculofugal arterial systems and, therefore, hypoxic-ischemic lesions in this age group are mainly concentrated in periventricular regions (periventricular leukomalacia). In term newborns, the vascular border lies between the anterior and middle and the middle and posterior cerebral arteries in the cortex, a distribution that corresponds to that of parasagittal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Laminar necrosis and the spongy change were mainly observed at the parasagittal cortex and subcortex around the arterial border zone, which suggested that partial prolonged asphyxia would be responsible for the development of the lesion. 30,31 Although neither severe hypotension nor brady cardia were observed during the hypoxic insult, profound ischemia as well as asphyxia could have been responsible for developing such injury at the arterial border zone.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the grey matter and underlying white matter in parasagittal areas is observed in a proportion of asphyxiated term neonates in many studies (Baenziger, Martin, Steinlin, Good, Largo, Burger, Fanconi, Duz, Buchli & Rumpel, 1993; Barkovich & Truwit, 1990; Campistol, Poo, Alvarez, Fernandez & Carratala, 1999; Kuenzle, Baenziger, Martin, Thun‐Hohenstein, Steinlin, Good, Fanconi, Boltshauser & Largo, 1994; Miller et al , 2005; Westmark, Barkovich, Sola, Ferriero & Partridge, 1995). Blood flow to this region has also been found to decrease during the period of acute illness (Volpe, Herscovitch, Perlman, Kreusser & Raichle, 1985).…”
Section: Patterns Of Brain Damagementioning
confidence: 99%